Analisis Kelayakan Booklet Pembuatan Lipbalm Bahan Alam Ekstrak Daun Karamunting dan Kayu Secang sebagai Sumber Belajar Matakuliah Bioteknologi: Feasibility Analysis of Lip Balm Making Booklet from Natural Ingredients of Karamunting Leaf and Secang Wood Extract as a Learning Resource for Biotechnology Course - Damayanti, Dera; Lestariningsih, Nanik; Ayastussa’adah, Ayastussa’adah (Information Technology and Science (ITScience), 2025)
Learning is an interactive process between educators and students; the goal is to achieve optimal learning outcomes. Learning resources are an important component to support the learning process, especially in the field of biotechnology. Adequate learning resources can improve student understanding and facilitate practical activities. Initial analysis shows that students are still less familiar with the use of booklets as learning resources, with 76.7% of students not familiar and 86.7% rarely used. The development of a booklet on lip balm with natural ingredients is important. This booklet presents information clearly and attractively. This research method uses R&D with the ADDIE model, involving two expert validators to assess the feasibility of the booklet. The validation results show that the developed booklet meets the feasibility criteria with values ??of 85.5% and 81.6% in the first stage and 95.5% and 97.5% after improvement. The developed booklet is suitable for use as a learning resource for biotechnology courses. Thus, it is hoped that this booklet can improve student motivation and learning outcomes in biotechnology courses.